2018
DOI: 10.19080/adoh.2018.10.555779
|View full text |Cite
|
Sign up to set email alerts
|

The Oral Health Status and Attitudes of Saudi Adolescent Male Students in Albaha Province: A Cross-Sectional Study

Abstract: Objectives: To explore and examine the oral health status of Saudi adolescent male students aged 12-15 years in Albaha province and evaluating the oral health attitudes of this population. Methods: This was a cross-sectional study in which random sampling was used. Data was collected at schools of the subjects between November 2017 and February 2018. A clinical examination was carried out to evaluate the presence of tooth decay, plaque and gingival bleeding. Then a face-to-face interviews with the study partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Also, the percentage of children with no previous visits to a dentist was high (38.3%) [34]. Another study found that most of the children participating went to the dentist for illness-related issues rather than preventative care [10, 35, 36]. One-third of the children visit a dentist only when they have pain [36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the percentage of children with no previous visits to a dentist was high (38.3%) [34]. Another study found that most of the children participating went to the dentist for illness-related issues rather than preventative care [10, 35, 36]. One-third of the children visit a dentist only when they have pain [36].…”
Section: Resultsmentioning
confidence: 99%
“…One-third of the children visit a dentist only when they have pain [36]. Among schoolchildren, factors that led to not using dental services included parental attitudes and anxiety, including “lack of time” and “logistic problems” [25, 35].…”
Section: Resultsmentioning
confidence: 99%
“…Since the implementation of the well-being framework. The prevalence of dental caries is high in Saudi populations, especially among young people [ 9 ]. Nationally, the prevalence of caries among children between the ages of 6 and 7 was 74% to 90% in the primary teeth.…”
Section: Introductionmentioning
confidence: 99%